2017
DOI: 10.1212/wnl.0000000000004646
|View full text |Cite
|
Sign up to set email alerts
|

Optimal deep brain stimulation site and target connectivity for chronic cluster headache

Abstract: Objective:To investigate the mechanism of action of deep brain stimulation for refractory chronic cluster headache and the optimal target within the ventral tegmental area.Methods:Seven patients with refractory chronic cluster headache underwent high spatial and angular resolution diffusion MRI preoperatively. MRI-guided and MRI-verified electrode implantation was performed unilaterally in 5 patients and bilaterally in 2. Volumes of tissue activation were generated around active lead contacts with a finite-ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…18 Another open-label study has shown that after 5 years of follow-up, all patients had a benefit with a reduction in episode frequency from 90% to 50% associated as well with a decrease in the perception of pain intensity. 16 DBS, however, does not abort acute attacks. 21 In an open prospective study with follow-up 34 ± 14 months, seven patients with refractory CCH, a MRI-guided and MRI-verified electrode implantation was performed unilaterally in five patients and bilaterally in two.…”
Section: Clinical Studiesmentioning
confidence: 92%
See 4 more Smart Citations
“…18 Another open-label study has shown that after 5 years of follow-up, all patients had a benefit with a reduction in episode frequency from 90% to 50% associated as well with a decrease in the perception of pain intensity. 16 DBS, however, does not abort acute attacks. 21 In an open prospective study with follow-up 34 ± 14 months, seven patients with refractory CCH, a MRI-guided and MRI-verified electrode implantation was performed unilaterally in five patients and bilaterally in two.…”
Section: Clinical Studiesmentioning
confidence: 92%
“…Four patients with bilateral cluster headache showed no improvement while three patients developed tolerance after experiencing relief in the first 1-2 years. 16 Data from long-term follow-up studies indicate that long-term hypothalamic stimulation is necessary to produce sensory and nociceptive changes for a prophylactic effect to develop, which starts to show mostly after several weeks of start of stimulation. 19 A randomized prospective crossover, double-blind (with sham stimulation) study in 11 patients during 1-month periods, followed whereas three patients were considered as treatment failures.…”
Section: Clinical Studiesmentioning
confidence: 99%
See 3 more Smart Citations